FILOSOFI GETHUK SEBAGAI WAY OF LIFE MASYARAKAT JAWA: DISPOSISI PENDIDIKAN ISLAM - Al Halim, A. Adibudin; Robingun Suyud El Syam (Jurnal Tawadhu, 2025)
The research objective is focused on exploring the gethuk philosophy as a way of life for Javanese society: the disposition of Islamic education. Qualitative descriptives were chosen to be used in this research, with library data sources. The results show that for the Javanese people, the Gethuk philosophy is a way of life to be guided by. Cassava as the main ingredient in gethuk is a symbol of the meaning of simplicity. Cassava plants can grow anywhere, but they remain humble by not showing their fruit. Meanwhile, the grated coconut that completes the getuk dish is a symbol of usefulness. All parts attached to the coconut plant are useful for humans. From the combination of cassava and coconut, it can be concluded that gethuk is a traditional food that reflects the meaning of simplicity and usefulness of human life. On the other hand, the use of cassava as a staple food to replace rice can be interpreted as a way for people to always bring innovation from various simple things around them. This philosophy is a disposition of Islamic education which teaches: humility, gratitude, simplicity, usefulness, and creativity in life. This research hopes to contribute to Islamic education regarding the philosophical meaning of food.